Protein fraction of latex Calotropis procera protects against induced oral mucositis 5-Fluorouracil in hamsters through inhibition proinflammatory mediators - Ana Paula Fragoso de Freitas (2011)
Oral mucositis (OM) induced by antineoplasic drugs is an important, dose-limiting, and costly side effect of cancer therapy. Calotropis procera is a plant plant constitutively produces abundant latex that is reported to possess anti-inflammatory, bacteriolytic, insecticidal, analgesic properties. The present work aimed to describe the effect of laticifer proteins of Calotropis procera (LP) in the expression of pro-inflammatory cytokines and inducible enzymes, such as, cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) in the model of OM in Hamsters. OM was induced by two intraperitoneal (i.p.) administrations of 5-Fluorouracil (5-FU) on the 1st and 2nd days (60 and 40 mg/kg, respectively) in hamsters (n=5). LP (0,25; 1; 5 E 25 mg / kg) was injected i.p. 24h before and 24h after mechanical trauma of the cheek pouches. Control group received only saline. On the 10th day, the animals were sacrificed and tissues from the cheek pouches were harvested. Macroscopical and histopathological (inflammatory cell infiltration, edema, hemorrhage and the formation of ulcerations and abscess) analysis as well as immunohistochemistry for TNF-, IL-1β, iNOS and COX-2 was performed in the cheek pouch tissue. Kruskal Wallis/Dunn was used as statistical tests. P<0.05 was accepted. Ethics Committee 036/10. The LP significantly inhibited macroscopical and histopathological parameters when compared to control group with maximum effect in macroscopic scores reaching 75% and 66% of maximum effect at the histopathological evaluation. The MPO activity was also significantly inhibited by LP in 91% at the same dose (p<0,001) and also inhibited the lost weight of 5- FU induced-oral mucositis. The cheek pouches of hamsters submitted to OM showed marked immunostaining for TNF-, IL-1β, iNOS and COX-2 on inflamed conjunctive (Cj) and epithelial (Ep) tissue compared with the cheek pouches of the normal control group. LP caused considerable reduction in the immunostaining for TNF- (62%,Cj; 70%,Ep), IL-1β (87%,Cj; 80%,Ep), iNOS (82%Cj; 52%Ep) and COX-2 (70%,Cj; 100%,Ep) in the check pouches tissue when compared with the group of animals subjected to experimental mucositis that received saline instead of LP. These findings show anti-inflammatory effects of LP in 5-FU-induced OM. The protective effect could be supported by the reduction of the expression of pro-inflammatory cytokines, such as TNF- and IL-1β and the enzymes iNOS and COX-2. The protective mechanism appears to involve inhibition of the expression of iNOS, COX-2, TNF-, and IL- 1β.